The effect of Learning Method and Adversity Intelligence on Student Learning Outcomes - Nur Hidayat; Yayat Ruhiyat; Nurul Anriani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Learning outcomes are fundamental elements in education that shape the direction of learning experiences and provide a concrete path for academic success. This study aims to determine the influence of adversity intelligence and learning approaches on student learning results. This study employs a factorial design, specifically a 2 x 2 factorial design. The target population and sample for this research consist of Class XI students enrolled at SMKN 1 Keramatwatu during the 2023/2024 academic year. The research sample consisted of one hundred class XI pupils, selected from a total population of two hundred individuals. This research employed random sampling procedures to achieve the appropriate sample size for their investigation. The research findings indicate that there are notable disparities in the impact of learning methods on student learning outcomes (F = 7.911 and Sig. value = 0.005 <0.05). Additionally, there are significant variations in the influence of adversity intelligence on student learning outcomes (F = 7.922 and Sig. value = 0.001 < 0.05). Furthermore, there is a significant interaction effect between learning methods and adversity intelligence on student learning outcomes. This study demonstrates that educators has the capacity to employ a wide range of effective teaching methodologies in order to enhance students' learning outcomes. In addition, educators have the capacity to evaluate students' resilience and adaptation in both academic and non-academic settings.